1980
DOI: 10.1111/j.1600-0722.1980.tb01220.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro development of chlorhexidine resistance in Streptococcus sanguis and its transmissibility by genetic transformation

Abstract: – Three chlorhexidine‐sensitive strains of Streptococcus sanguis developed resistance to chlorhexidine when grown as continuous cultures in a fermenter containing medium with increasing concentrations of the drug. The MIC of the test strains increased by between two and three dilution steps and these high values were maintained after daily transfer in drug‐free medium for at least 15 d. In addition, the resistance of one of the strains persisted for more than 1 month of continuous growth in drug‐free medium in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…1). Little is known about adaptation to CHX, although it has been shown that strains of S. sanguis can develop resistance in vivo (Emilson and Fornell, 1976) and when grown in increasing concentrations of CHX in vitro (Westergren and Emilson, 1980). The data from our pH-fall studies also suggest that the community had become more resistant to CHX after pulsing (Table 3), although this was not substantiated by measurements of the inhibition of glycolytic rates (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…1). Little is known about adaptation to CHX, although it has been shown that strains of S. sanguis can develop resistance in vivo (Emilson and Fornell, 1976) and when grown in increasing concentrations of CHX in vitro (Westergren and Emilson, 1980). The data from our pH-fall studies also suggest that the community had become more resistant to CHX after pulsing (Table 3), although this was not substantiated by measurements of the inhibition of glycolytic rates (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Their concentrations, however, were low compared with those in the present study (0.07-0.15 mM CHX and 4-8 mM F vs. 1.98 mM CHX and 53 mM F, re spectively), and hardly any effect on viability was ob served after treatment with the solutions of the low concentrations. Apparently, the less concentrated so lutions applied in the clinical situation, the less side effects are to be awaited [Meurman, 1986], Another problem, however, may arise if S. mutans strains also develop resistance to CHX as has been shown to l e the case with Streptococcus sanguis strains [Wester gren and Emilson, 1980], In the present series the S. mutans cells did not show any increased staining in the electron micro graphs after CHX treatment when compared with the controls (see figures 1-4). We have earlier observed a distinct increase in electron density at cell walls oi bacteria in subgingival plaque samples treated with 2% CHX when compared with those treated with sa line [Meurman and Asikainen, unpubl.].…”
Section: Discussionmentioning
confidence: 99%
“…One agent which has been shown to inhibit the formation of dental plaque in both short-term and longterm clinical studies is chlorhexidine (Gjermo and Eriksen, 1974;Joyston-Bechal et al, 1979;Loe and Rindom Schi0tt, 1970). Development of bacterial resistance to chlorhexidine is rare (Davies et al, 1954;Hennessey, 1973;Rindom Schi0tt et al, 1976;Westergren and Emilson, 1980). This is perhaps because chlorhexidine does not act on specific protein receptors or enzymes as do many antibiotics, but rather exerts its inhibitory effect by a generalized perturbation of the bacterial membrane Longworth, 1964, 1965).…”
mentioning
confidence: 92%